2018
DOI: 10.1126/sciimmunol.aao2892
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory killer cell immunoglobulin-like receptors strengthen CD8 + T cell–mediated control of HIV-1, HCV, and HTLV-1

Abstract: Killer-cell immunoglobulin-like receptors (KIRs) are expressed predominantly on natural killer cells, where they play a key role in the regulation of innate immune responses. Recent studies show that inhibitory KIRs can also impact adaptive T cell-mediated immunity. In mice and in human T cells in vitro, inhibitory KIR ligation enhanced CD8+ T cell survival. To investigate the clinical relevance of these observations, we conducted an extensive immunogenetic analysis of multiple, independent cohorts of HIV-1, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(91 citation statements)
references
References 88 publications
(85 reference statements)
2
87
0
2
Order By: Relevance
“…Correlating with direct impact on both NK cell development and effector function (Freud et al 2017;Vivier et al 2011), numerous studies have implicated combinatorial diversity of KIR and HLA class I alleles with the course of specific infectious and autoimmune diseases, as well as the success of transplantation (Boudreau and Hsu 2018;Holzemer et al 2017). Importantly, the quantity as well as quality of these interactions can influence individual responses to infection (Boelen et al 2018;Pelak et al 2011). Thus, the polymorphism of KIR and HLA class I has profound impact on human health.…”
Section: Introductionmentioning
confidence: 99%
“…Correlating with direct impact on both NK cell development and effector function (Freud et al 2017;Vivier et al 2011), numerous studies have implicated combinatorial diversity of KIR and HLA class I alleles with the course of specific infectious and autoimmune diseases, as well as the success of transplantation (Boudreau and Hsu 2018;Holzemer et al 2017). Importantly, the quantity as well as quality of these interactions can influence individual responses to infection (Boelen et al 2018;Pelak et al 2011). Thus, the polymorphism of KIR and HLA class I has profound impact on human health.…”
Section: Introductionmentioning
confidence: 99%
“…While studies have focussed on the cytotoxic action of NK cells, these lymphocytes may also apply indirect effects via interactions with the adaptive immune system. A recent study into the control of viral load within infected cells by NK cells found that iKIR exerted influence upon the CD8 + T cell response . This study showed that HLA‐B57 provides a protective quality, reducing the viral load in this patient cohort, and HLA‐B35 presents a detrimental effect, with these individuals more susceptible to high viral loads.…”
Section: Kir and Haemopoietic Progenitor Cell Transplantationmentioning
confidence: 61%
“…This study showed that HLA‐B57 provides a protective quality, reducing the viral load in this patient cohort, and HLA‐B35 presents a detrimental effect, with these individuals more susceptible to high viral loads. iKIR was found to exacerbate this effect, in both a beneficial capacity (in association with HLA‐B57) and in a detrimental capacity (in association with HLA‐B35), by extending the lifespan of CD8 + T cells . The iKIR on the surface of the T cell was found to have a direct effect on the T cell, but iKIR on NK cells may also exert an indirect influence.…”
Section: Kir and Haemopoietic Progenitor Cell Transplantationmentioning
confidence: 95%
“…In vivo, even if a cell's intrinsic programme is age-dependent, randomly encountered cell-exogenous stimuli such as cytokines, cell-cell contact or antigen may render its resultant behavior age-independent. That is, lymphocytes may have an age but other factors dominate in vivo so in practice age does not determine their fate (49). Of note, in many of the in vitro experiments supporting the cyton model, autocrine Il-2 is blocked (20,24,50).…”
Section: Discussionmentioning
confidence: 99%